The Role of Digital Evidence in Criminal Law Enforcement: Challenges of Authentication and Admissibility in Court - Achyarsyah, Padri; Riyadi, Sugeng; Widodo, Kusno; Chamim, Mochammad; Faisal, Faisal (Research Horizon, 2025)
Digital evidence has become a crucial element in modern criminal law enforcement in Indonesia, particularly in addressing cybercrimes such as online gambling, online fraud, and data theft. This study aims to analyze the legal standing of digital evidence, the challenges of its authentication and admissibility in court, and strategies to ensure its reliability in the judicial process. The study uses a normative juridical method with descriptive analysis through statutory and conceptual approaches, based on a study of legal regulations, court decisions, academic literature, and digital forensic guidelines. The results show that digital evidence has been legally recognized through the Criminal Procedure Code (KUHAP), the ITE Law, and Supreme Court regulations, as long as its authenticity and integrity can be proven. However, major challenges remain, including the potential for data manipulation, limited infrastructure, and a lack of competent human resources. Efforts to ensure the reliability of digital evidence include the implementation of standard forensic procedures, capacity building of law enforcement officers, cross-agency collaboration, the use of advanced technology, and strengthening an adaptive legal framework to support effective law enforcement and public trust.